KREATIVITAS DALAM PEMBELAJARAN MUSIK - Herwin Yogo Wicaksono (LPMPP Universitas Negeri Yogyakarta, 2009)
This study aimed to reveal (1) the difference in students motivation to learn music, and (2) the difference in the ability to play music between the students taught with creativity elements in learning music and those taught without them. This study employed a pretest-posttest control group design. The data were analyzed by the descriptive technique and t-test. The research subjects were Year V students of SD Negeri Sinduadi, Mlati, Sleman. The research results showed the following. (1) In the experimental group, students motivation to learn music was higher than that in the control group (tobserved = 4.330; p 0.05). It was concluded that there was a difference in students motivation to learn music between those taught with creativity elements in learning music and those taught with the conventional method. (2) In the experimental group, the ability to play music was better than that in the control group. It was concluded that there was a difference in students ability to play music between those taught with creativity elements in learning music and those taught with the conventional method.Keywords: music learning, creativity, motivation